Super President: The History and Future of Executive Power in South Africa (Bhaso Ndzendze) - Bailie, Craig (Scientia Militaria - South African Journal of Military Studies, 2025)
Super President: The History and Future of Executive Power in South Africa by Bhaso Ndzendze, Johannesburg: UJ Press, 2024, 240 pages, ISBN 978-1-7764-9001-1.